2013
DOI: 10.1093/ntr/ntt068
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Price Minimization Strategies in the United States: Price Reductions and Responsiveness to Excise Taxes

Abstract: introduction: Because cigarette price minimization strategies can provide substantial price reductions for individuals continuing their usual smoking behaviors following federal and state cigarette excise tax increases, we examined independent price reductions compensating for overlapping strategies. The possible availability of larger independent price reduction opportunities in states with higher cigarette excise taxes is explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
0
18
0
6
Order By: Relevance
“…This is also known as the ‘pass-through rate’. The majority of the existing literature, with the exception of two papers [20,21], suggests that the overall pass-through rate of excise taxes in the United States is greater than or equal to 1.0 (also known as over-shifted) [2027]. In addition, consistent with economic theory, global evidence has also shown that cigarette or alcohol excise taxes are not passed homogeneously to all users [2026,2831].…”
Section: Introductionmentioning
confidence: 99%
“…This is also known as the ‘pass-through rate’. The majority of the existing literature, with the exception of two papers [20,21], suggests that the overall pass-through rate of excise taxes in the United States is greater than or equal to 1.0 (also known as over-shifted) [2027]. In addition, consistent with economic theory, global evidence has also shown that cigarette or alcohol excise taxes are not passed homogeneously to all users [2026,2831].…”
Section: Introductionmentioning
confidence: 99%
“…The per pack price reductions associated with these strategies ranged from $0.26 for using price promotions to as much as $1 for purchasing cigarettes by the carton. The size of these price reductions may be increasing with rising cigarette excise taxes: the price reductions for carton purchasing were previously estimated at $0.68 in 2006–07 (Pesko et al, 2013) and is estimated at $0.99 in this research in 2009–10, during which time 21 states increased their cigarette excise taxes at least once and the federal government increased its excise tax from $0.33 to $1.01 a pack. Our findings suggest that price-sensitive smokers may have low-priced alternatives that allow them to continue to purchase cigarettes within their budget when facing price increases.…”
Section: Discussionmentioning
confidence: 62%
“…We performed regression analysis to account for overlapping price reductions. Except for one 2006–2007 study with limited strategies (Pesko et al, 2013), this approach has not been used in other studies of cigarette price reductions (DeCicca et al, 2010; Hyland et al, 2004; Licht et al, 2011a; White et al, 2005; Xu et al, 2013). We also focus on the strategy of price promotions by investigating if individuals receive differential price reductions from this strategy depending on cigarette brand.…”
Section: Introductionmentioning
confidence: 99%
“…18 However, for price/taxation policies to achieve the desired effect of reducing overall tobacco use among price-sensitive individuals, due attention must also be given to tobacco industry interference which might attenuate the impact of taxation measures, such as use of rebates or couponing schemes. 19 In addition, an integrative approach towards taxation of different tobacco products may be necessary to avert or reduce price-minimization strategies, such as switching to relatively cheaper products such as hand rolled cigarettes, as previously noted in South Africa. 20 This study found some striking disparities in smoking among certain population groups.…”
Section: Discussionmentioning
confidence: 99%